Philosophy of truth and metaphor between heritage and modern linguistic thought - Nimer, Mustafa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Truth and metaphor are fundamental and thorny issues in the critical and rhetorical heritage. The ancients have made great efforts to provide a theoretical and procedural basis; however, religious and philosophical factors have prevented these efforts from reaching their desired goals. Hence, the need for a new scientific and objective approach to this issue has emerged, illustrating philosophy. Which was characterized by its problems, in light of the data provided by the modern linguistic lesson. In this approach, this research attempted to address the concept of truth through the axises of de Saussure, and the constraints of procreation in the generatives. The metaphor sought to address it through a range of issues: substitutional displacement, superficial structure, deep structure, and media efficiency.